GROWTH OF Thalassiosira sp AND Chaetoceros sp. IN SCALE OF LABORATORY, INTERMEDIATE AND MASSAL - Kurniaji, Ardana; Wahid, Eriyanti; Regan, Yip; Rasnijal, Muhammad; Normayanti, Novi (Politeknik Kelautan dan Perikanan Dumai, 2025)
The availability of high-quality live feeds, such as Thalassiosira sp. and Chaetoceros sp., is a critical factor for the success of shrimp aquaculture; however, it is often constrained by fluctuations in growth performance and cell density at different production scales. This study aimed to identify the growth of Thalassiosira sp. and Chaetoceros sp. at laboratory, intermediate, and mass scales. The research was conducted using an experimental method with a Completely Randomized Design (CRD) with two treatments and three replications. The treatments were different microalgae species cultured at different production scales and compared. Cell density data and growth phases were analyzed statistically using SPSS. The results showed that Chaetoceros sp. had higher growth compared to Thalassiosira sp. The cell density range of Chaetoceros sp. was 1.1×10⁷ - 5.0×10⁷ cells/mL, while Thalassiosira sp. was 1.7×10⁶ - 5.2×10⁶ cells/mL. The growth rate of Chaetoceros sp. also reached the peak of the exponential phase faster at Day of Culture (DOC) 4 compared to Thalassiosira sp., which peaked at DOC 5. Water quality during the study across all production scales showed an optimal range for the growth of both microalgae species.